Mobile Phone Use and Brain Tumor: An Age-Period-Cohort Analysis of Brain Tumor Rates in the Nordic Population - Ranjbaran, Mehdi; Khodadost, Mahmood; Mansori, Kamyar; Mousavi Jarrahi, Seyed Houssien; Ayubi, Erfan; Nazarzadeh, Milad; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Cancer Biology, 2016)
Background: The association of the mobile phone use and risk of brain tumor remains controversial among radiation epidemiologists. Methods: We hypothesized if an association between brain tumor and mobile phone use exists, this association will be manifested as a cohort effect (as a proxy of association between mobile phone use and brain tumor) in the incidence rates of brain tumor during the period of 1990 to 2009. We used age-period-cohort methodology (generalized log-linear model) and compared the distribution of cohort effects in the observed rates of brain tumor from 1990 to 2009 to the cohort effects from rates driven based on epidemiological study results that reported a positive association between brain tumor and mobile phone use in the Nordic population. Three latency period of 1-4 years with odds ratio (OR) of 1.2, latency period of 5-9 years with OR of 1.3, and latency period of more than 10 years with OR of 2.7 were used to estimate expected rates. Results: The distribution of cohort effects between observed and expected rates were more similar among the males compared with females. A shorter latency was more con¬sistent to observed rates. Conclusion: Our study supports a possible a weak association between mobile phone use and brain tumor; further fueling the controversies in association.